An evaluation of the system performance of alarm and vehicle detection (AAVD) through internet of things (IoT) - Abdul Hamid, Norihan; Jasny, Muhammad haziq hazmani; Ibrahim, Mazree (2023)
Nowadays, Nowadays, an alarm and vehicle detection (AAVD) system is a necessity for many vehicles security such as a car, motorcycle, lorry and etc. The system promises better security awareness and vehicle tracking movement from any location at any time. In this paper, AAVD was designed and implemented specifically for motorcycle as a means to overcome the increment of stolen motorcycle cases in the community every year. The system is equipped with an alarm alert system that will be activated automatically when there is an attempt of theft, which also includes tracking movement detection in case the motorcycle is successfully stolen. Owner will be notified immediately through SMS if any strangemovement is detected from their motorcycle. Not only that, alarm will be triggered and vehicle location tracking is then activated. The global positioning system (GPS) module is used to track the location of the vehicle in the form of latitude and longitude value. These values are transmitted to the owner through a GSM module via Short Message Services (SMS). This simple communication of interconnected devices between vehicle and other electronic devices that has the capabilities to detect, notify, alarm and track is what made up an Internet of Thing (IoT) technology implementation in the system. Atthe end of this paper the AAVD system was successfully designed and assembled on a Yamaha, 110cc motorcycle. An analysis showed that about 74% of power was consumed for microcontroller, GSM and GPS module due to the signal stability requirement from transmitter to receiver. The accuracy of location detection was within 5-meters radius in theopen sky and 20 meters inside the building.